Exergy and energy performance for wavy fin radiator with a new coolant of various shape nanoparticle-based hybrid nanofluids - Kumar V.; Sahoo R.R. (My University, 2025)
Energetic and exergetic performance for an automotive radiator with wavy fin configuration has been investigated and compared for water-based 1% vol. fraction of hybrid nanofluids of different shapes of nanoparticles, i.e., spherical (Al2O3) and cylindrical (CNT), spherical (Al2O3) and platelet (graphene) shapes at 15l pm flow rate. Effects of effectiveness, heat transfer rate and pressure drop, as well as exergy loss, entropy generation, second law efficiency with steady-state coolant flow rate, hybrid nanofluid vol. fractions and air velocity are discussed well. Results show that energetic–exergetic performances are enhanced by using the hybrid nanofluid of different shapes of nanoparticles. Nanoparticles of spherical (Al2O3) and cylindrical (CNT)-based hybrid nanofluid show the decrement in performance within the study. Nanoparticles of different shapes have been delivered a promising effect on both parameters (irreversibility and second law efficiency) and are increases with coolant flow rate. Spherical and platelet-shaped nanoparticle-based hybrid nanofluid has 2.94% 1.73% and 1.62% of higher effectiveness, entropy change in the air and coolants, respectively, compared to hybrid nanofluid of spherical and cylindrical shape nanoparticles. This inspection divulges on the particle shape, which has a critical consequence on the accomplishment of hybrid nanofluids in automotive radiators and the application of spherical and graphene shape nanoparticle-based hybrid nanofluid is more effective to enhance the radiator performance. © 2020, Akadémiai Kiadó, Budapest, Hungary.